Enhancing Water Treatment with an Innovative Filtration Method - Kundewar, Shubhangi; Salunke, Omkar; Jadhav, Lakhan; Sakhare, Rushikesh; Deshmukh, Leena A (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
Purification has always been a necessity since the dawn of humanity. Purification is important for decreasing the risk of toxins from recharging runoff rainwater and avoiding numerous ailments. As a result, the national and state governments in India are developing water treatment plants to provide society with adequate and safe drinking water. Rapid sand filters are commonly used in India to remove suspended and colloidal particles from water in the filtering process at a faster rate by laying down separate sand beds. The usage of a sand filter as a technique is taken into consideration. In industry, it is often used to remove impurities from water and wastewater treatment. The filtration process degrades at the beginning and end, affecting the initial quality of the filtrate following backwashing. Filter to waste, delay start, sluggish start, and filter conditioning by coagulant during backwashing are all examples of waste to cope with initial filtrate quality problems. In addition, the use of coconut shells in filtration serves as a dual media filter. Designing a 'Dual media filter covered with crushed coconut shells' is more efficient, cost- effective, and long-lasting. It increases the filter's performance in terms of high filtration rate, increased filter run, reduced backwashing requirements, and high turbidity removal, making it more suitable for a variety of applications.